Race and Prejudice: Constructing Identity in “The Help” Movie - Afifulloh, Muhammad; Saputra, Arfian Dwi; Theresa, Gracia Petra; Kurnia, Happy; Setyawan, Tedi; Dwitama, Wahyu Rismayuda (EEdJ: English Education Journal, 2024)
This study aimed to describe and analyze the representation of racism in the film "The Help." The research method used were descriptive qualitative and content analysis to identify how the concepts of racism, stereotypes, and power displayed in the film's narrative. The theory used in this study was the "Theory of Prejudice" proposed by Gordon Allport, which helps in understanding how negative perceptions of certain groups can develop into discriminatory attitudes and actions. The results of this study provide deep insight into how racism was presented in entertainment media and its impact on social consciousness. It was found 12 acts of discrimination that has been divided into 4 four types such as verbal antagonism, avoidance, segregation, and physical attack.